Water cold plates for high power converters: A software tool for easy optimized design. (September 2018) - Cova, P.; Delmonte, N.; Chiozzi, D.; Portesine, M.; Vaccaro, F.; Mantegazza, E.
Abstract: This work proposes a SPICE-CFD/FEM based methodology for an optimized design of water heatsinks for high power electronic converters. Cold plates are a key issue for power electronics systems, in order to obtain reliable applications. Often the design of custom heatsinks is done by manual procedures, which require the fabrication of several prototypes. On the other hand, CFD + FEM analysis is a powerful tool to design optimized cold plates, but it requires skilled technicians and long simulation studies. In this paper a SPICE based methodology, with negligible simulation cost and limited use of CFD + FEM simulations and prototypes, is demonstrated to be adequate to design cold plates with the lowest thermal resistance and the lowest surface temperature gradient. A prototype made with the proposed methodology was used to validate the approach. Results show a good agreement between cold plate thermal-fluid dynamic 3D numerical simulations and the SPICE based methodology. A software tool was developed to easily exploit the proposed methodology in customized design of cold plates for any specific application, and to extract necessary data for the datasheet: pressure drop, and thermal resistance.